Investigation of oxidative stress in experimental periodontitis treated with myricetin - Gulsoy, Zehra; Pinar Keles Yucel, Zeynep; Guven, Berrak; Balli, Umut (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate the effects of systemically applied myricetin on oxidative stress and antioxidant status in experimental periodontitis of rats.Materials and Methods: 24 Wistar rats were used and randomly divided into three groups. Experimental periodontitis was induced by placing a silk ligature around first molars teeth of the rats for 15 days. Following removal of the ligatures, Group 1: saline; Group 2: myricetin and Group 3: doxycycline were administered systemically. Total antioxidant status (TAS), total oxidant status (TOS), oxidative stress index (OSI), superoxide dismutase (SOD) enzyme and malondialdehyde (MDA) levels in serum; and SOD and MDA levels in gingival tissue were determined by biochemical analysis.Results: Serum TAS increased and serum TOS and OSI values decreased in myricetin and doxycycline treated groups compared to saline group (P0.016). Gingival tissue SOD activity was increased in the group treated with doxycycline compared with the group treated with saline (P0.016). MDA levels in both serum and gingival tissue samples were decreased in myricetin and doxycycline treated groups compared to saline group (P0.016).Conclusion: The systemic administration of myricetin may be useful to diminish oxidative damage in periodontitis.